PENGARUH KEUNIKAN PRODUK TERHADAP PEMBELIAN IMPULSIF TILLANDSIA DENGAN HARGA SEBAGAI VARIABEL INTERVENING DI GIOFLORIST - Herwin, Herwin; Meliana, Vina (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to analyze the effect of product uniqueness on impulsive purchases with price variables as intervening variables Design/methodology/approach- Quantitative methods are used to explain the relationship between variables with multiple regression analysis.Findings- Product Unique Variables and Price Variables affect the Impulsive Purchase variable, the Price Variable affects the Impulsive Purchase variable. And the price variable is not an intervening variable between the Unique Product variable and the Impulsive Purchase variableImplication/Limitation - Then the company can prioritize the Product Uniqueness variable first because it provides the greatest influence compared to the price variable in creating Impulsive Purchases. Keywords: Product Uniqueness, price, Impulsive Buying, Tillandsia